2017
DOI: 10.1371/journal.pntd.0005279
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocytes Kill Brugia malayi Microfilariae Independently of DNA-Based Extracellular Trap Release

Abstract: BackgroundWuchereria bancrofti, Brugia malayi and Brugia timori infect over 100 million people worldwide and are the causative agents of lymphatic filariasis. Some parasite carriers are amicrofilaremic whilst others facilitate mosquito-based disease transmission through blood-circulating microfilariae (Mf). Recent findings, obtained largely from animal model systems, suggest that polymorphonuclear leukocytes (PMNs) contribute to parasitic nematode-directed type 2 immune responses. When exposed to certain patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 37 publications
5
47
0
Order By: Relevance
“…Thus, typical NET characteristics were here confirmed for D. immitis -induced NETs by co-localization experiments on microfilariae and L3-triggered release of extracellular DNA being adorned with histones, NE and MPO. In accordance to studies on other metazoan parasites, L3 and microfilaria-triggered NETosis revealed as time dependent ( 47 50 , 56 ). In line with data on B. malayi, Haemonchus contortus, Strongyloides stercoralis , and other metastrongyloid species ( 47 50 ), NETs were dissolved via DNase I treatment thereby proving the DNA nature of these structures.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, typical NET characteristics were here confirmed for D. immitis -induced NETs by co-localization experiments on microfilariae and L3-triggered release of extracellular DNA being adorned with histones, NE and MPO. In accordance to studies on other metazoan parasites, L3 and microfilaria-triggered NETosis revealed as time dependent ( 47 50 , 56 ). In line with data on B. malayi, Haemonchus contortus, Strongyloides stercoralis , and other metastrongyloid species ( 47 50 ), NETs were dissolved via DNase I treatment thereby proving the DNA nature of these structures.…”
Section: Discussionsupporting
confidence: 89%
“…So far, most studies on parasite-triggered NETosis focused on protozoan parasites ( 38 45 ). By contrast, little data exist on metazoan-triggered NET formation ( 46 50 ). In the case of filariae, the reports on NETosis come exclusively from Brugia malayi and L. sigmodontis , in which microfilariae/L3 were recently demonstrated as potent triggers of NETs leading to parasite entrapment but not killing in vitro ( 24 , 50 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that resistance to gastrointestinal nematodes in sheep increases with age, and as such, results obtained utilizing a ewe model of infection may differ compared to those using lambs. In addition, human neutrophils have been shown to bind and effectively kill the microfilaria of Brugia malayi in vitro in a manner similar to what is presented here …”
Section: Discussionsupporting
confidence: 64%
“…When Brugia malayi microfilariae were incubated with human polymorphonuclear leukocytes (PMNs), the PMNs released ETs that capture the microfilariae. However, after the DNase was added into the medium, the DNase eliminated the PMN attachment to microfilariae ( McCoy et al, 2017 ). The enzyme DNase II has been detected in the ES and surface proteins of T. spiralis AW, IIL, and ML stages, and it affects the host immune system ( Cui et al, 2013b ; Wang et al, 2014 , 2017 ; Liu et al, 2016a ,b).…”
Section: Discussionmentioning
confidence: 99%